Predictors and etiology of healthcare-associated infections in patients with severe community-acquired pneumonia - I. A. Ruslyakova; E. Z. Shamsutdinova; O. V. Dmitrieva; K. I. Shirokov; Yu. V. Borzova; A. E. Orishak; N. V. Vasilyeva (Вестник анестезиологии и реаниматологии)
Introduction. The increasing prevalence of healthcare-associated infections (HAIs) caused by critical, high and medium priority pathogens among patients with severe community-acquired pneumonia (SCAP) and the high mortality rate necessitate monitoring of pathogens and consideration of predictors.The objective was to identify predictors, determine the etiology and evaluate the dynamics of pathogens of HAIs over a 10-year period in patients with SCAP.Materials and methods. An analysis of medical records of 756 patients treated in the intensive care unit was of the I.I. Mechnikov NWSMU was conducted in the period from 2013 to 2023. Incidents of HAIs (catheter-associated urinary tract infection – CAUTI, catheter-associated bloodstream infection – CLABSI) and ventilator-associated pneumonia – VAP) were determined in accordance with the NASCI criteria from 2023.Results. The study included 663 patients with SCAP. The density of HAIs in patients with SCAP was 6.2/1000 days of device use (DDU) and shows an increase in the period 2021–2023. The frequency of CLABSI caused by multiple drug resistance (MDR) pathogens was 69.2%, CAUTI 24.4%, VAP 42.9%. 72 cases of HAI were registered in 67 patients, of which 24 (35,8%) patients with SCAP had 50 critical and high priority pathogens, of which 16 (23.8%) had bacterial-fungal associations. The priority pathogens in the registration of DAIs for the entire analyzed period were carbapenem-resistant strains of A. baumannii and K. pneumoniae as well as K. pneumoniae isolates resistant to third-generation cephalosporins. A trend towards expanding the spectrum of pathogens and increasing the proportion of Candida non-albicans in the etiological structure of fungal HAIs was identified in the period 2021–2023. Independent predictors of DAIs were identified in patients with SCAP, which were > 7 DDU for CLABSI, and > 72 hours of mechanical ventilation for VAP, and an increase in procalcitonin > 0.5 ng/ml for VAP and CAUTI. When registering CAUTI, the severity of comorbidities (CCI score ≥ 5: 3.829; 1.867–7.852, p < 0.001) in patients with SCAP and the severity of organ dysfunction (SOFA score > 4.0 (9.976; 1.277–77.958, p = 0.028) in patients with SCAP COVID-19 were independent predictors of HAIs.Conclusion. In the period 2021–2023, an increase in HAIs was observed in the group of patients with SCAP. The main pathogens of which were critical, high and medium priority pathogens K. pneumoniae, A. baumannii, as well as Candida spp. (C. tropicalis, С. parapsilosis, P. kudriavzevii). Independent predictors of HAIs in patients with SCAP were identified, which were the duration of use of devices and the increase in the level of procalcitonin above 0.5 ng/ml. When registering CAUTI, risk factors such as the severity of comorbidities for patients with SCAP and the severity of organ dysfunction in patients with SCAP COVID-19 were identified.